Comparative Analysis of Outcome Between Extravesical and Transvesical Repair for Vesicovaginal Fistula - Ali, Adnan; Shehzad, Khubaib; Mirza, Zahoor Iqbal; Ahmed, Hussain; Tabassum, Shazia; Changezi, Nisarefatima (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the surgical outcome of extravesical and transvesical repair of Vesicovaginal fistula. Study Design: Prospective comparative study. Place and Duration of Study: Armed Forces Institute of Urology, Rawalpindi Pakistan, from Jul 2019 and Jul 2020. Methodology: Forty-two patients with vesicovaginal fistula were included in the study. The causes of the development of vesicovaginal fistula were evaluated. Half of the patients underwent extravesical and remaining transvesical repair. The results were compared regarding operative time, mean blood loss, complications and recurrence. Results: The vesicovaginal fistula was secondary to prolonged obstructed labour 27(66%), with an iatrogenic cause 15(34%).Mean operative time for extravesical repair was 83.00±20.00 minutes and for transvesical repair was 60.00±20.00 minutes.71% patients undergoing extravesical repair experienced bladder spasms compared to 47% in the transvesical Group. Three cases suffered prolonged illeus in case of extravesical repair. The mean hospital stay for extravesical repair was 6.00±1.08 days,relatively more than transvesical, which was statistically significant (p-value <0.001) Conclusion: Transabdominal approach for managing vesicovaginal fistula is the most preferred successful technique.